Néo-conservatisme contre Universalisme - Frank Romano (Revue LISA)
This study will first set forth the principles underpinning universalism and neo-conservatism, followed by the re-launching of the polemic which pits neoconservatives against universalism, the former seeking to privilege the American Empire. The setting up and the support of international structures has become necessary for a true protection of human rights and true cooperation in the face of war and other conflicts. This requires the enhancement of a new concept, that of unification of the human race by unification of legal principles and by their universal application. The conflicts between nations give rise to the necessity for universal structures, such as an international tribunal capable of pursuing international anticompetitive practices, as well as those accused of genocide and crimes against humanity. Thus, a universalistic approach within a legal framework becomes fundamental for justice, even for the survival of humanity. However, American interventionist and neoconservative policy flies in the face of a universal movement. It advances rather the notion of the American Empire, which attempts to impose itself with impunity throughout today’s world. Moreover and extraordinarily, the Bush Administration succeeded in bringing together two opponents, the neoconservative and Fundamentalist Christian movements, which, together, block the progression of the universalistic movement towards a more balanced and evolved human race. As such, does the neoconservative movement, which encourages the development of this Empire, push the world into a downward anti-universal spiral? Does it even threaten to jeopardize our very survival? So-called universalism is the proposed answer to this threat. The antithesis to universalism is a political movement created in the United States: neoconservatism.